Malaysia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1994)
This paper describes economic developments in Malaysia during the 1990s. Real output growth strengthened to 8 1\2 percent in 1993 from 7 3/4 percent in the previous year. In contrast to 1992, however, growth in output was driven exclusively by domestic demand, with all components recording stronger growth in 1993 than in the previous year. Consumption spending grew by 7 3/4 percent in 1993, up from 2 3/4 percent in 1992. Fuelled by higher real wages and the positive wealth effect of higher equity prices, real private consumption rose by 7 1\2 percent in 1993, compared with 2 1\2 percent in 1992.